Interconnected Lamellar 3D Semiconductive PCP for Rechargeable Aqueous Zinc Battery Cathodes - Lin, Zirui; Otake, Ken‐ichi; Kajiwara, Takashi; Hiraide, Shotaro; Nurhuda, Maryam; Packwood, Daniel; Kadota, Kentaro; Sakamoto, Hirotoshi; Kawaguchi, Shogo; Kubota, Yoshiki; Yao, Ming‐Shui; Horike, Satoshi; et al. (Small (Weinheim an der Bergstrasse, Germany), 2025)
2D electronically conductive porous coordination polymers/metal–organic frameworks (2D EC‐MOFs) of M‐HHTPs (HHTP = 2,3,6,7,10,11‐hexahydroxytriphenylene; M = Co, Ni, Cu, etc.) have received extensive attention due to their ease of preparation, semiconductive properties, and tunability based on the choice of metal species. However, slight shifts between layers attenuate their specific surface area and stability. In this study, the metal‐ion bridge strategy is newly adopted and a vanadyl counterpart of M‐HHTP is synthesized with a chemical formula of (VO)3(HHTP)2, hereafter referred to as VO‐HHTP. The semiconductor VO‐HHTP has a vertical interconnection by octahedral VO6 chains and exhibits a relatively high specific surface area (ca. 590 m2 g−1) compared to other 2D EC‐MOFs. Motivated by its redox activity and porous nature, VO‐HHTP is applied as the cathode material in rechargeable aqueous zinc batteries (RAZBs). VO‐HHTP demonstrates a high capacity of 240 mAh g−1 and excellent rate capability, even with a reduced amount of conductive agent, surpassing the performance of the previous EC‐MOFs. Furthermore, its stable structure ensures long‐term cycling stability, addressing a common issue in previous EC‐MOFs. The work contributes to the development of new concepts in both the design of π‐conjugated EC‐MOFs and the study of cathode materials for RAZBs. VO‐HHTP, a 2D electronically conductive metal–organic framework (EC‐MOF) featuring vanadyl oxide (VO2+) centers and 2,3,6,7,10,11‐hexahydroxytriphenylene (HHTP) ligands, achieves robust interlayer interactions and organized stacking. This innovative structure significantly boosts its performance as a cathode for rechargeable aqueous zinc batteries, delivering higher capacity, superior rate capability, and enhanced cycling stability, surpassing existing materials.